Harmonisasi Awig-Awig dan Undang-Undang Nomor 32 Tahun 2009 dalam Penegakan Hukum Pencemaran Lingkungan Pesisir di Nusa Lembongan - Bhyasa, Putu Paramaditya Bhaskara; Sri Rahayu, Anak Agung Ayu Ngurah (Lembaga Teewan Journal Solutions, 2026)
The rapid growth of tourism in Nusa Lembongan has strengthened the local economy but has also increased the risk of coastal environmental pollution from hotels, restaurants, and marine tourism activities. Environmental protection is governed through the coexistence of awig-awig (customary law) and Law Number 32 of 2009 on Environmental Protection and Management. Differences in their principles and enforcement mechanisms create challenges in achieving effective environmental governance. This study aims to analyze the challenges of harmonizing awig-awig with Law Number 32 of 2009 and to identify strategies for strengthening environmental law enforcement against coastal pollution. An empirical legal research design was employed using statutory and factual approaches. Data were collected through interviews, observations, documentation, and literature review, and analyzed qualitatively. The findings indicate that harmonization is constrained by weak coordination between customary and government institutions, differences in enforcement procedures, and the lack of integration between customary and statutory sanctions. Effective harmonization requires aligning the provisions of awig-awig with national legislation, strengthening institutional coordination, increasing community participation, and improving the supervision of tourism-related business activities. Integrating customary and state legal systems can enhance environmental law enforcement, strengthen legal certainty, and support the long-term sustainability of Nusa Lembongan’s coastal environment.